Effect of temperature on the life history parameters of noctuid lepidopteran stem borers, Busseola fusca and Sesamia calamistis - Khadioli, N.; Tonnang, Henri E.Z.; Ong'amo, G.; Achia, Thomas; Kipchirchir, I.; Kroschel, Jürgen; Le Ru, B. (Wiley, 2014)
The influence of temperature on the development, mortality, fecundity and life table parameters of two important noctuid African cereal pests, Busseola fusca and Sesamia calamistis was investigated under laboratory conditions. Experiments were carried out with larvae reared on artificial diet under eight constant temperatures (12°C, 15°C, 18°C, 20°C, 25°C, 28°C, 30°C and 35°C) and a 12L:12D photoperiod. Life table parameters were calculated using Insect Life Cycle Modelling (ILCYM) software. At 12°C and 35°C insects failed to develop. Mean development time for both species decreased with increasing temperature for all stages. Between 15°C and 30°C, mean larvae development time is divided by four for both species and adult mean longevity is divided by 1.5 and 2.5, for both sexes of S. calamistis and B. fusca, respectively. Fecundity varied according to temperature; the highest was estimated at 22°C and 24°C for B. fusca and S. calamistis, respectively. The lower thermal threshold for B. fusca and S. calamistis was, respectively, 6°C and 9°C, while the upper thermal threshold was 31°C and 32°C, respectively. The highest intrinsic rate of natural increase for B. fusca was obtained at 25°C while for S. calamistis it was obtained at 28°C. The highest net reproduction was obtained at 25°C for both species, but it was higher for S. calamistis than for B. fusca. The shortest population doubling time was observed at 25°C for B. fusca and at 28°C for S. calamistis. The optimum temperature range for development of both species was 25–28°C. The lower lower thermal threshold found for B. fusca than for S. calamistis and the higher upper thermal threshold found for S. calamistis than for B. fusca explain in part the observed distribution of both species in sub‐Saharan Africa with S. calamistis occurring in all the agro‐ecological zones but being usually more common than B. fusca in savannah lowland and B. fusca reported mainly from mid and high altitude areas.